[BP.04.04] ATP2B1 VARIANT RS2854371 G/A GENOTYPE ASSOCIATED WITH ASYMPTOMATIC INTRACRANIAL ATHEROSCLEROTIC STENOSIS IN STROKE-FREE HYPERTENSIVE CHINESE. (September 2017) - An, D.; Wang, Y.; Gao, P.; Zhu, D.
Abstract : Objective: Intracranial atherosclerotic stenosis (ICAS) is considered as a risk factor of ischemic stroke, especially in those with hypertension. Meanwhile, ATP2B1 gene has been associated with hypertension and vascular stiffness by several studies. We hereby aim to test the association of ATP2B1 common variants with ICAS in stroke-free hypertensive Chinese. Design and method: A Total of 881 consecutive hypertensive patients without stroke were included. They were 50 years or older, without severe cardiovascular disease and able to receive CTA examination. Patients were divided into ICAS and Non-ICAS (NICAS) group according to CTA results. 11 tag SNPs were selected, which covered the ATP2B1 gene and 20 kb of flanking sequences to either side. Figure. No caption available. Results: There were 330 patients in ICAS group and 551 in NICAS group. Rs2854371showed significant association with ICAS. The patients with G/A genotype had increased ICAS prevalence (OR:1.59; 95%CI: 1.17–2.16) after adjusted for age, sex, BMI, antihypertensive treatment, systolic blood pressure, LDL, HDL, smoking status, and diabetes. A-allele of Rs2854371was associated with an increased susceptibility to ICAS (OR 1.42; 95% CI: 1.06–1.91). In the subgroup analysis, G/A genotype remained significant in females (OR:2.2; 95% CI:1.39–3.46), non-diabetes (OR: 1.68; 95% CI: 1.17–2.39) and non-smokers (OR:1.55; 95% CI: 1.11–2.17, p = 0.022). Compared with the G/G carriers, patients with G/A genotype were found to have more intracranial atherosclerotic lesions (P = 0.013). Conclusions: In conclusion, rs2854371 G/A genotype of ATP2B1 gene was associated with increased susceptibility of asymptomatic ICAS in a hypertensive Chinese population, especially in females, non-diabetes and non-smokers.